Sediment transport relations in alluvial channels - Kodoatie, Robert J., author; Albertson, M. L., advisor; Simons, Daryl B., committee member; Grigg, Neil S., committee member; Julien, Pierre, committee member; Smith, Freeman M., committee member (Colorado State University. Libraries, 2000)
This dissertation presents new methods for predicting sediment transport in alluvial channels. The new methods were developed based on simple equations and easy-to-apply parametric relationships and can be applied to a wide range of river conditions. Modifications of Posada (1995), Simons et al. (1981) and Laursen (1958) equations and Laursen graph with a wide range of field and flume data are presented. The first step was to test the applicability of 10 selected sediment transport relations, including Einstein (1950), Laursen (1958), Bagnold (1966). Toffaletti (1969), Shen & Hung (1972), Ackers & White (1973), Yang (1973). Brownlie (1981). Karim & Kennedy (1981) and Karim (1998) using field data of alluvial rivers. Review and evaluation of some of the com parison results between computed and measured sediment discharges by previous researchers were conducted. A summary of the selected equations which had the best fit of sediment transport to the measured values is also presented. The relation and correlation of hydraulic geometry and sediment characteristics to the sediment transport rates were examined carefully. Velocity, slope, flow depth, and dimensionless unit stream power which have best correlation for various river-beds and river channel sizes to the measured sediment transport rate were used to modify one or two existing equations. Using statistical approaches and non-linear optimization, simple sediment transport relations were developed so they can be easily applied and be used for practical purposes. A total of 4532 datasets from 33 river system s in the United States of America. South America, and Asia were used for analysis and verification. The field data were divided randomly into two groups; one for analysis and the other for validation and verification. In addition, 919 sets of laboratory data from 19 sources were added to verify the proposed methods. The data were divided according to the mean diameter particle of river-bed materials ranging from silt to gravel, including silt-bed rivers, very fine to fine sand-bed rivers, medium to very coarse sand-bed rivers, and gravel-bed rivers. The data also were grouped according to river size, including small rivers, intermediate rivers and large rivers.
Keywords: civil engineering; geography; physical geography